EVALUASI KEBERLANJUTAN MASYARAKAT BADUY DALAM BERDASARKAN COMMUNITY SUSTAINABILITY ASSESSMENT - Mieske Widyarti; Hadi Susilo Arifin (http://arl.faperta.ipb.ac.id/, 2012)
Nowadays human settlements are using a large amount of fossil fuels and natural resources that produce pollutions. Environment quality is degrading each year causing many disaster occurring all over the world including Indonesia. Today settlements are continuously being built by new technologies which is advanced in techniques and materials, but lack of environmental consideration. Societies who are concerning in environmental degradation can lead to the unsustainable living in the world has developed a community called Global Ecovillage Network (GEN). GEN concluded that to save the world from an extinction people, way of live need to be changed in a more environmentally friendly manner. This way of live is popularly known as ecovillage. People need to be more economic, efficient and live harmoniously with all organism in the nature. Global Ecovillage Network (GEN) has developed a tool called Community Sustainability Assessment (CSA) which defined level and ways to be more sustainable in a community.Indigenous people, The Inner Baduy community as an indigenous people, is well known since 16th century and still exists until now. They have developed systems from their longstanding experience as their local wisdoms than can adapt to their environment in a sustainable manner.The aim of this study is to emphasize the importance of traditional knowledge in terms of providing low input energy, water and wastes to the natural resources in a settlement scale. The study results are concept and level of sustainability of Inner Baduy community based on CSA.